Enhancing students’ thinking skills through project-based learning in biology - Denny Muhammad Fajar; Murni Ramli; Joko Ariyanto; Sri Widoretno; S Sajidan; Nanik Murti Prasetyanti (Biosfer: Jurnal Pendidikan Biologi, 2020)
This research aims to enhance students' thinking skills (TS) through a project-based learning (PBL) intervention in two cycles of classroom action research (CAR) on the topic of the Ecosystem. TS was determined by the quantity and quality of the students' questions (SQ) and statements (SS), which were determined based on Bloom's taxonomy. The research target was students in grade X (N=31) of one social science class at a public high school in Surakarta. Their TS were rated as low during the Pre-cycle. Based on their verbal activities, the students were categorized into five active (A) and non-active (NA) groups (A-1, A-2, NA-1, NA-2, and NA-3). The NA students were more engaged after the two cycles of CAR. Although the A-1 and A-2 students posed more SQ and SS than the NA students, some of the NA-1, NA-2, and NA-3 students performed positively. In the Pre-cycle, only the C1 and C2 cognitive levels were detected, mostly as factual and conceptual. During the CAR, however, C4, C5, and C6 were found as procedural. In Cycle II, we can find a few examples of metacognition. Overall, this research has shown that PBL can be used to increase student learning engagement. They become active communicators. There was evidence that the quality of students' questions and statements improved to the level of C6 and metacognition. Hopefully, further research can be conducted on the impact of grouping strategies during PBL activities by purposively combining high-achieving students or actively questioning and giving their peers statements in the opposite situation.